The struggle against poverty, unemployment and social injustice in present-day South Africa: Exploring the involvement of the Dutch Reformed Church at congregational level - Van der Westhuizen, Marichen; Swart, Ignatius (Stellenbosch Theological Journal, 2016)
This article is based on an exploration of the involvement of the Dutch Reformed Church (DRC) at congregational level in the struggle against poverty, unemployment and social injustice in present-day South Africa. The exploration arises from the thesis that South African citizens continue to regard poverty, unemployment and social injustice as the key challenges to be met in order to build a healthy nation. Historically, the DRC acted as a prominent partner of the government to address the basic needs of the poor and the sick, especially among the country’s white population. But the structural and social changes that followed the transformation to the new democratic South Africa impacted significantly on this partnership. This in turn required that the role of the DRC in addressing social issues in the country be revisited. The essential purpose of this article is, firstly, to provide better insight into the nature and extent of the current social services rendered by congregations of the DRC in addressing the challenges of poverty, unemployment and social injustice; and secondly, from this vantage point, to present some recommendations in conclusion on how the DRC could, in terms of its own striving towards even deeper and more effective social engagement, further enhance its contribution to address the identified challenges at congregational level.